A scanning ion imaging investigation into the micron-scale U-Pb systematics in a complex lunar zircon - Bellucci, J.; Whitehouse, M.; Nemchin, Alexander; Snape, J.; Pidgeon, Robert; Grange, Marion; Reddy, Steven; Timms, Nicholas (Elsevier Science BV, 2016)
© 2016 Elsevier B.V.The full U-Pb isotopic systematics in a complex lunar zircon 'Pomegranate' from lunar impact breccia 73235 have been investigated by the development of a novel Secondary Ion Mass Spectrometry (SIMS) scanning ion imaging (SII) technique. This technique offers at least a four-fold increase in analytical spatial resolution over traditional SIMS analyses in zircon. Results from this study confirm the hypothesis that the Pomegranate zircon crystallized at 4.302 ± 0.013 Ga and experienced an impact that formed, U-enriched zircon around primary zircon cores at 4.184 ± 0.007 Ga (2s, all uncertainties). The increase in spatial resolution offered by this technique has facilitated targeting of primary zircon that was previously inaccessible to conventional spot analyses. This approach has yielded results indicating that individual grains with a diffusive distance of less than ~. 4 µm have been reset to the young impact age, while individual grains with a diffusive distance larger than ~. 6 µm have retained the old crystallization age. Assuming a broad range in cooling rate of 0.5-50 °C/year, which has been observed in a suite of similar lunar breccias, a maximum localized temperature generated by the impact that reset small primary zircon and created new, high-U zircon is estimated to be between 1100 and 1280 °C.